Management of Lateral Semicircular Canal Benign Paroxysmal Positional Vertigo - Zuma e Maia, Francisco; Ramos, Bernardo Faria; Cal, Renato; Brock, Camila Martins; Mangabeira Albernaz, Pedro Luiz; Strupp, Michael (Frontiers in Neurology, 2020)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of peripheral vestibular vertigo. It is caused by free-floating otoconia moving freely in one of the semicircular canals (canalolithiasis) or by otoliths adhered to the cupula (cupulolithiasis). The posterior canal is the most common canal affected, followed by the lateral canal. Diagnosis of the side affected is critical for successful treatment; therefore, suppressing visual fixation is essential to examination of these patients' eye movement. On the basis of our experience, we have adopted the Zuma maneuver and the modified Zuma maneuver for both apogeotropic and geotropic variants of lateral canal BPPV. Knowledge of the anatomy and pathophysiologic mechanisms of the semicircular canals is essential for correct management of these patients. Hence, using a single maneuver and its modification may facilitate daily neurotological practice.